Teaching English to Young Learners in a Virtual Classroom - Anatasyah, Widya; Ahmad, Yousef Bani; Al-Baekani, Abdul Kodir (Peneliti.net, 2024)
This research investigates the experiences of a seasoned teacher who specializes in teaching English to young learners through virtual means. Virtual learning has gained popularity due to its numerous benefits, and the teacher in question possesses a strong background in language and experience with virtual learning, even prior to the government’s implementation of online learning policies during the pandemic. The study explores various lessons encountered by the teacher in her virtual classroom, including learning methodologies, maintaining motivation among young learners during distance learning, and addressing challenges and difficulties. Through comprehensive interviews with the teacher and corroborating evidence from other sources, this study demonstrates the value of teaching English to young learners through virtual means. Utilizing narrative inquiry as a research design, this study presents all significant findings in a narrative format. The results comprise eight key lessons for other language teachers to implement in their own classrooms, whether virtual or direct learning. These lessons include the teacher’s motivation, choice of media, learning methodologies, learning objectives, learning activities for young learners, practical application of English in real life, and exploration of young learners’ language skills during the learning process.